Injuries associated with resuscitation – An overview. (July 2015) - Olds, Kelly; Byard, Roger W.; Langlois, Neil E.I.
Abstract: External cardiopulmonary resuscitation is a potentially lifesaving intervention aimed at preserving the cerebral function of a person in cardiac arrest. However, certain injuries can be caused by the various techniques employed. Although these are seldom consequential, they may complicate the forensic evaluation of cases. Fractures of the ribs and sternum are the most common internal injuries and are frequently acknowledged as a consequence of resuscitation. Nonethlesss, the recognition that less common fractures such as of the larynx or injuries involving the stomach, spleen, heart and liver can occur due to resuscitation will assist the forensic examiner assess the significance of these findings when they present in cases of sudden death. Highlights: In 1960, Kouwenhoven et al. developed a method of resuscitation using external cardiac massage. Injuries from resuscitation may complicate forensic evaluation of cases. Potential external, internal and multiple system findings are reviewed. Injuries resulting from automated resuscitation devices are also considered.